A COMPREHENSIVE EVALUATION OF HOSPITAL INFORMATION SYSTEMS BASED ON THE HOT-FIT FRAMEWORK - Wardhana, Erdianto Setya; Yaniawati, Poppy; Santoso, Budi (Indonesian Journal of Dentistry, 2025)
Background: The advancement of information technology requires hospitals to manage information systems efficiently. However, RSIGM Sultan Agung Semarang still encounters difficulties in optimizing its Hospital Management Information System (HMIS) to support daily operations and strategic decisions. This study aims to examine the influence of human, organizational, and technological factors on the net benefits of HMIS, both individually and collectivelyMethod: A mixed-methods design with convergent triangulation was employed, integrating qualitative and quantitative data. Qualitative insights were obtained through in-depth interviews with key stakeholders, while quantitative data were gathered via a structured, validated questionnaire distributed using total and stratified random sampling.Result: The results showed that organizational and technological factors had a significant positive effect on the perceived net benefit of HMIS, with organizational support identified as the most influential. In contrast, the human factor demonstrated a significant negative impact, suggesting user-related barriers to system use. Collectively, the three factors explained a considerable portion of the variance in net benefit.Conclusion: The study concluded that strengthening organizational systems and advancing technological components were essential for enhancing HMIS performance. Addressing human factors through targeted training and simplifying system interfaces was also necessary to improve user experience and satisfaction